2020
DOI: 10.3389/fvets.2020.572064
|View full text |Cite
|
Sign up to set email alerts
|

Milk Replacer Supplementation Ameliorates Growth Performance and Rumen Microbiota of Early-Weaning Yimeng Black Goats

Abstract: Increasing evidence has indicated the ameliorative effect of milk replacer supplementation in ruminants for regulating their early growth and rumen development. However, it is still unclear whether milk replacer supplementation has a beneficial role in the growth performance and rumen microbiota of Yimeng black goats (YBGs). Therefore, this study was performed to investigate the effects of milk replacer on growth performance and rumen microbiota of YBGs. Our results revealed that milk replacer supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…At the phylum level, the ratio of Firmicutes in the gut microbiota of milk replacer-treated YBGs increased, whereas the ratio of Cyanobacteria , Actinobacteria and Proteobacteria decreased as compared to control YBGs. Remarkably, our previous study also indicated that milk replacer supplementation significantly reduced the abundance of Actinobacteria in the rumen of YBGs [ 14 ]. The Firmicutes is mainly responsible for the digestion of cellulose and its higher abundance in the intestinal environment contributes to meet the nutrition and energy requirements of animals during growth and development [ 31 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…At the phylum level, the ratio of Firmicutes in the gut microbiota of milk replacer-treated YBGs increased, whereas the ratio of Cyanobacteria , Actinobacteria and Proteobacteria decreased as compared to control YBGs. Remarkably, our previous study also indicated that milk replacer supplementation significantly reduced the abundance of Actinobacteria in the rumen of YBGs [ 14 ]. The Firmicutes is mainly responsible for the digestion of cellulose and its higher abundance in the intestinal environment contributes to meet the nutrition and energy requirements of animals during growth and development [ 31 ].…”
Section: Discussionmentioning
confidence: 88%
“…Hu et al found that the alpha diversity of piglets was apparently decreased during the early period after weaning due to the sudden diet transition from breast milk to solid feed [ 28 ]. Our previous research has demonstrated that milk replacer administration could not change the diversity of rumen microbiota of early-weaned YBGs, but the composition of the rumen microbiota has changed [ 14 ]. In the current study, we noticed that the milk replacer administration had no effects on the structure and diversity of the gut bacterial community of YBGs, which may be the results of the similarity in composition and physical structure of milk replacer and breast milk without causing stress response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have distinct long necks and legs, off-white skin patches separated by white-off white color, and a pair of ossicones (horn-like structure) on their head. Microbiota of the gastrointestinal tract plays an important role in digestion in ruminants and G. camelopardalis (2)(3)(4). This gut microbiota, particularly in the rumen, plays vital roles in gut homeostasis, host immunity, and physiology (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%